Thermal characteristics in a tube fitted with inclined vortex rings - Koolnapadol, Narin; Chingtuaythong, Witoon; Promvonge, Pongjet; Kwankaomeng, Sutapat (My University, 2014)
The paper presents an experimental study on the heat transfer, pressure loss and thermal performance characteristics in a round tube fitted repeatedly with inclined vortex ring (VR) under a uniform wall heat flux. Periodically VRs are inserted into the tube with a view to generating vortex flows that assist to increase the heat transfer rate of the tube. The airflow rate in terms of Reynolds number is ranging from 5000 to 25,000. Measurements are carried out for the VR with a single blockage ratio, BR= e/D = 0.1 and an attack angle, α = 20°, at fourVR pitch ratios, PR= P/D = 0.5, 1.0, 1.5 and 2.0. The variations of heat transfer and pressure loss are presented in the form of mean Nusselt number and friction factor respectively. The experimental results show that the use of the VRs leads to the considerable increase in heat transfer and friction factor values in comparison with the smooth tube. The VRs at PR = 0.5 provides the highest heat transfer and friction factor. © (2014) Trans Tech Publications, Switzerland.
Keywords: Friction loss; Turbulent flow; Vortex flow; Vortex ring